Diversiform Etiologies for Post-stroke Depression - Wang, Zan; Shi, Yanmin; Liu, Fangfang; Jia, Nan; Gao, Junya; Pang, Xiaomin; Deng, Fang (Frontiers in Psychiatry, 2019)
After the onset of stroke, many patients suffer from emotional behavior changes. Approximately, one-third of stroke survivors are affected by post-stroke depression (PSD), making it a serious social and public health problem. PSD has an important impact on the course, recovery and prognosis of stroke. The pathogenesis of PSD is very complex, involving many factors such as biological mechanism and social psychological mechanisms. This article provides a brief review of the hot issues related to etiologies of post-stroke depression.